Cytoplasmic 5-Lipoxygenase Staining Is a Highly Sensitive Marker of Human Tumors of the Choroid Plexus. Issue 2 (1st August 2015) - Xingfu, Wang; Lifeng, Zhang; Yupeng, Chen; Xueyong, Liu; Wei, Liu; Yinghao, Yu; Suqin, Cai; Mi, Wang; Sheng, Zhang
Abstract: Objectives: To determine the immunoreactivity status of 5-lipoxygenase (5-LO) in normal tissues, in tumors of the human choroid plexus, and in other brain tumors. Methods: In total, 135 cases of various types of brain tumors were selected. Tissue samples were immunostained with a rabbit polyclonal anti–5-LO antibody. Results: Nuclear reactivity was observed in most brain tumors, with most of the positive tumor cells exhibiting low-level reactivity. Cytoplasmic strong immunoreactivity for 5-LO (2+ or 3+) was only observed in 8.8% of astrocytic tumors, 0% of oligodendrogliomatous tumors, 5.6% of ependymal tumors, 0% of embryonal tumors, 3.1% of meningeal tumors, and 0% of metastatic lung adenocarcinomas. In contrast, cytoplasmic immunoreactivity for 5-LO was detected in all 27 cases of choroid plexus tumors. Twenty-five cases showed strong and diffuse cytoplasmic immunoreactivity. Conclusions: Our findings indicate that cytoplasmic 5-LO immunoreactivity is highly characteristic of human choroid plexus tumors but not other central nervous system tumor types. Cytoplasmic staining for 5-LO may prove to be a useful immunoreactive marker in the diagnosis of choroid plexus tumors.